Decrypting the Phaistos Disk: Gareth Owens at TEDxHeraklion (TEDx Heraklion, 2014)
: Καλησπέρα σας, από την κρίτη μας, και καλησπέρα σας από το πέμπαιο. Δεν μπορώ να διαβάζω τη μορφή μου, αλλά όταν ξεκινάω να ξεχάσω πράγματα, καθώς δουλεύω στις οικογένειες, εργασίας και εργασίας, ελπίζω ότι θα με αφήσουν. Ήμουν ξεκάθαρος επειδή του Σαντ Βαλαντιντίνα, αλλά τώρα φοβάμαι πως είναι επειδή του αγώνα και της μικρής χαράς που έχω. Λοιπόν, εδώ είναι. Βέβαια, το Κρήτον για τους αγαπημένους είναι το Άγιος Ιακίνθος, πάνω από το Ψιλωρίτι, το Μαύρο Τάιδα, και η συνεργασία είναι το 3ο Ιουλίο, το ίδιο μέρος που βρήκε το Φέστος από τους Ιταλικούς Αρχαιολογούς στη Κρήτη. Τίκαιο, δεν ομίζω. Και όταν ήρθα πρώτα στον Κρήτο, είχα λευκά χαρά και ένα μυαλό. Τώρα, το μικρό χαρά που έχω είναι λευκό. Υπάρχουν θεωρήσεις για να εξηγήσει αυτό. Είμαι ο κοινοβουλευτής για μια ελληνική κοινοβουλία. Ένα πολύ δύσκολο concept για να εξηγήσει, πιστεύω. Αλλά πράγματι, όπως συχνά στη δημόσια κοινωνία και στο προβλήμα, η απάντηση είναι πάντα μια συγκομμή θεωρήσεων. Και παρακαλώ, σήμερα θα συμβ I'm a co-ordinator for a Hellenic University. A very difficult concept to translate, believe me. But probably, as so often in popular science and problem solving, the answer is usually a combination of theories. And please remember, tonight we're going to combine reading, but that is not automatically the same as understanding. Tonight we're going to have synergy and synergism. I came to Crete from the UK for six months, 25 years ago. So the first idea worth spreading is, expect the unexpected. I am now 15, I've spent half my life here in Crete. Indeed, I hope it's half of my life, should I be lucky and healthy enough to make it to 100. As Sir Arthur Evans was 90, and we still have a lot of hard work ahead of us with the Festus Disc. By the way, Sir Gareth was the youngest knight of the Round Table of King Arthur, looking for the Holy Grail. That is, searching for the truth. I was actually born in the same hospital as Sir Mick Jagger in the UK. So thanks to my family for that start in life. And as the Rolling Stones' good friend Andy Warhol said, in the future everybody will be famous for 15 minutes. I think our generation knows that now. So today it's my turn, and I would like to share some ideas with you over the next 15 minutes concerning life, international education, research on the Festus Disc, but all evolving, revolving, sorry, around the great island of Crete that we are lucky enough to live in. We would like to share our reading of the Festus Disc, and please remember that a pleasure shared is a pleasure doubled. And a trouble shared is a trouble halved. Please also remember that to read does not mean automatically to understand. And we are not just talking about the infamous Festus Disc, of course. Here I show you syllabic writing of Festus along with the key word on the disc. Crete has offered me a family, health, career, health usually, career in international education with Erasmus Plus at the TE and research on the Minoan language and the Festus Disc. I list the offerings in that order deliberately, and I am grateful. Crete for me represents culture and respect in European technology and education. Crete is our cultural compass strategically situated at the crossroads of civilizations between the three continents of Europe, Asia, and Africa. Crete is not paradise. A Persian Farsi word meaning garden, but it could be close. Crete is our guide, thanks to NASA, on our odyssey of understanding in the labyrinth of life. The great island of Crete and indeed the infamous Festus Disc could well be a metaphor for life. Crete is at the crossroads between the Celtic West and Indian East, European North and African South. Indeed, Minoan Crete is the Mediterranean origin of Europe, and Nikos Katsantzakis said, as we all know, it is a great responsibility to be Cretan. That is to be philotimos, to be a decent human being. Crete is from where Europe started, and we should respect her values, especially as we recently celebrated 100 years since the union of Hellas, Greece, with Crete. We should also respect how people think, even if and maybe especially if they think in a different way from us. The important point is to think, as many people I fear do not, and to positively enjoy the meeting of civilizations and not to negatively fear the clash of civilizations. Six years ago, we also celebrated another centenary anniversary, that of the discovery of the Festus Disc in the Mesera in South Crete on the 3rd of July 1908 at the Palace of Rathmanthus. In 2008, there was a meeting in London and I met John Coleman, Professor of Phonetics at Oxford, and we decided to combine resources, to share ideas, so as to try to produce the best possible reading of the Festus Disc, after a century of what can only politely be called fantasy. We combined ideas, shared thoughts, criticised each other's work, and most importantly, listened and learned, corrected and improved. In my opinion, it is easier to speak than to listen. John demonstrated that I had made a mistake in identifying the vowel sound, value of the head of the punk, as A on the Festus Disc, using statistical frequency, and not by using epigraphic continuity and the sound value A on the Arcalochori axe from central Crete, which can be read as I damana, and compared with Minoan linear A from Arcalochori that reads I damater. On the Festus Disc, we both agreed on the sign que, by using epigraphic continuity. That is that the same signs have the same sounds in the ancient Cretan writing systems. The key word on the Festus Disc starts with equa, and occurs 13 times out of 61 words. That's 20% of the time. 12 of these words occur on side A, so we could read the key word equa curia, which occurs three times, and we were beginning to make progress. When I accepted my mistake, then we both subsequently realised that the Festus Disc could be read by systematically applying the decipherment of Cretan-inspired Mycenaean linear B to the Minoan syllabic scripts. The way forward was indeed through epigraphic continuity and partial parallel texts. What I would like to share with you today here on Crete is our reading of the disc, and our odyssey of understanding in the linguistic labyrinth, on our way to our own Ithaca at Festus in the Mesera and South Crete. It was necessary to have collaboration, constructive criticism, and correction in the learning process. Sometimes it is indeed necessary to take a step back in order to progress. In the labyrinth of life, do not be afraid to go back and try again. There is always a better way if we want to find it. There is a win-win scenario. What we must do is to dare to try, to listen, to work together, and don't be afraid in life to make mistakes. It took me a long time to realise that. Don't be afraid in life to make mistakes, but to still go ahead, preferably with a friend by your side. As we do not yet have a Minoan Rosetta Stone, nor the genius of Ventris, who deciphered linear B, and as we didn't get the Nobel for literature, then we must keep trying. Work harder and work as a team. Michael Ventris got good ideas for methodology from Alice Kober for deciphering linear B and got an OBE. Rosalind Franklin contributed significantly to the discovery of DNA for which Crick and Watson got a Nobel. Alan Turing brilliantly led the team of codebreakers at Bletchley Park, Station X, including John Chadwick, that cracked the Enigma code before the Battle of Crete in the Second World War. The famous Rosetta Stone is a bilingual inscription in the Greek and Egyptian languages, but it is a trigraphic inscription written in the Greek alphabet for the Greek language and in both Egyptian hieroglyphics and in Egyptian demotic writing for the Egyptian language. It was possible for Thomas Young to identify the key words such as Ptolemy as royal names in cartouches. And it was this that gave the clue to the linguistic labyrinth, or the crib plaintext way in, to use the terminology of Alan Turing at Bletchley Park. Jean-Francois Champollion subsequently used this to identify Cleopatra and to fully extend the decipherment of Egyptian hieroglyphics, and we know there is often no single eureka moment, but an ongoing process of lifelong learning. The secret of success is both hard work and teamwork, and we all know that history is neither black nor white, but is more like 50 shades of grey. Anyway, can we now read the Festus disk from the Messera, and what does it symbolise? At Tei or Eter, or for example here today at the Creta Aquarium. As you may well know, I usually avoid the word symbolism like the plague when talking about the Festus disk, but today let's consider the disk and Crete as metaphors. On the 1st of June, Ventris demonstrated that the Linear B tablet found by Evans at Knossos recorded the Mycenaean Greek language 1400 BC. This was 200 years before the Trojan War, and 700 years before Homer wrote down the Iliad and Odyssey in the Hellenic alphabet. The decipherment of Linear B, subsequently proved by the Pylos tripod tablet, the closest that we have to a Mycenaean Rosetta stone, can now be both adopted and adapted to the Minoan scripts and languages, including the Festus disk some 500 years before the Trojan War. There are 3,000 Mycenaean syllabic inscriptions, 2,000 Minoan syllabic inscriptions. That's 5,000 syllabic inscriptions from Crete. So why should the Festus disk and the Akhalahori Acts be treated any differently? We had found our methodology to systematically apply the decipherment of Linear B to the Festus disk through the Minoan syllabic scripts. We should learn from the past in order to find ways to solve future problems. And the best example is undoubtedly the Antikythera device, the first computer. This was solved by an international and interdisciplinary team of scientists working very hard indeed and who were also undoubtedly well funded. We must invest in education and research if we want positive results in the future. There is a lesson here for Greece in the current economic crisis. Europe is investing in Erasmus Plus and education and research until 2020. But cutting education in Greece will most definitely not bring positive results. We must educate ourselves out of a crisis. And who knows anyway, the Festus disk just might be the first CD-ROM. Play disk, read only Minos. But I believe there is always a solution and answer if we want to ask a good question. There is always a better way if we want to try. We now believe that we can literally read more than 90% of the Festus disk. We do so by systematically extending the decipherment of Linear B to the Minoan inscriptions including the disk using epigraphic continuity and parallel texts. Our results have been published on the TEI website by Dalica in order to be freely disseminated, constructively criticised, then corrected and subsequently improved. We now believe that it is indeed possible to read the disk and that the disk is now seriously studyable. Something unimaginable in my opinion six years ago. The next stage is of course more difficult but also potentially more rewarding. What does it actually mean? We can now offer a reading of 90%. On side A we have the key word ique 12 times and the same word is the first word on text on side B. We believe that the key word ique curia may mean mother and or goddess similar to the Mycenaean potinia iqueia potnia at Pylos. On side B there are five words which can undoubtedly be compared with and are related to the Minoan libation formula. On the best preserved Minoan religious inscription from Mount Yuktas above Knossos and Archanes found with Tamata votive offerings. The Minoan libation formula, the ten repeated words is what the Minoans of Bronze Age Crete wanted to say to their deity. Perhaps the mother goddess for matters of health and it can be found for certain on side B of the Festus disk. This Yuktas inscription, perhaps the closest that we have to a Minoan Rosetta stone has eight words. Six of which can be found on the Festus disk or on the Arcalachoriax. What did the Minoans actually want to say? That is the 14 million dollar question. We don't know yet. That's my favorite word recently. But it's also to be found on the Festus disk. And as John Coleman in Oxford who teaches computational linguistics so nicely put it. Without going through all the calculations it turns out that the probability that the nine signs in this portion of the Festus disk match these nine signs in the Yuktas libation formula just by being chance is over one in 14 million. So is the match just a coincidence? Highly unlikely. If any skeptic still thinks it is a coincidence and accepts these odds we bet you one euro that it isn't due to chance. When you finally admit you are wrong you will owe us 14 million euros. Cheers John what may be the closest that we have to a partial Minoan Rosetta stone with nine signs matching in the correct order. We can now read the disk but what does it mean? It is a genuine Minoan religious inscription. That much we can prove after six years of hard work and pleasant teamwork. After a previous century of not knowing Crete and the Festus disk have demonstrated the value of international collaboration, communication and friendship in the labyrinth of life. Our previous task over the last six years was to read the disk in the linguistic labyrinth and our next task over the next six years is to try to understand it. But it would be fitting and respectful to close for now with the voice of the Festus disk itself. With the kind assistance of Arati Alexopoulou from Festus and with Harry Polykronakis on the PC we also thank all who have so kindly helped us with my great Erasmus IT students from the TEI and Brunon in the Czech Republic. On the TEI di Dalical website we have done a sort of Jurassic Park for Minoan linguistics. I have the honour to be the co-ordinator of the team but anyway I know you didn't come for me, you came for the disk. The only thing that worries me is if we play it and the sharks talk back. I have a serious problem. This we offer you as a small thank you Antidoro for what Mother Crete has so generously offered us. Madonna might only need four minutes to save the world but we only need three minutes to read the Festus disk. Although it took us six years of hard teamwork to get there after being lost in the labyrinth but we are now perhaps on our way to understanding the Festus disk, the Minoan holy text. Ο δίσκος της Festus ανάγνωση από την Αρετή Αλεξοκούλου, Ιούνιος του 2013. Reading of the Festus disk by Areti Aleksopoulou, June 2013. Ο δίσκος της Festus ανάγνωση από την Αρετή Αλεξοκούλου, Ιούνιος του 2013. Ο δίσκος της Festus ανάγνωση από την Αρετή Αλεξοκούλου, Ιούνιος του 2013. Ο δίσκος της Festus ανάγνωση από την Αρετή Αλεξοκούλου, Ιούνιος του 2013. Ο δίσκος της Festus ανάγνωση από την Αρετή Αλεξοκούλου, Ιούνιος του 2013. Ο δίσκος της Festus ανάγνωση από την Αρετή Αλεξοκούλου, Ιούνιος του 2013. Ο δίσκος της Festus ανάγνωση από την Αρετή Αλεξοκούλου, Ιούνιος του 2013. Ο δίσκος της Festus ανάγνωση από την Αρετή Αλεξοκούλου, Ιούνιος του 2013. Ο δίσκος της Festus ανάγνωση από την Αρετή Αλεξοκούλου, Ιούνιος του 2013. Ο δίσκος της Festus ανάγνωση από την Αρετή Αλεξοκούλου, Ιούνιος του 2013. Ευχαριστώ.